2008
DOI: 10.1002/gps.2173
|View full text |Cite
|
Sign up to set email alerts
|

Patients' attitudes of dementia screening across the Atlantic

Abstract: SUMMARY Background Dementia is a common and growing global public health problem. It leads to a high burden of suffering for society with an annual cost of $100 billion in the US and $10 billion in the UK. New strategies for both treatment and prevention of dementia are currently being developed. Implementation of these strategies will depend on the presence of a viable community or primary care based dementia screening and diagnosis program and patient acceptance of such a program. Objective To compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 15 publications
1
48
0
1
Order By: Relevance
“…Four studies [30, 34, 36, 40] showed that in most cases the doctors felt that the individual was too ill to proceed with a full assessment or to use screening instruments. The clinicians tend to address other more easily treatable issues first rather than the dementia because they report making more impact.

“When we do see people for dementia, it is common that they have ten other medical problems.

…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [30, 34, 36, 40] showed that in most cases the doctors felt that the individual was too ill to proceed with a full assessment or to use screening instruments. The clinicians tend to address other more easily treatable issues first rather than the dementia because they report making more impact.

“When we do see people for dementia, it is common that they have ten other medical problems.

…”
Section: Resultsmentioning
confidence: 99%
“…Since our project, the SAPH has become the Perceptions Regarding Investigational Screening for Memory in Primary Care (PRISM-PC) questionnaire , Justiss et al, 2008. The PRISM-PC and the original SAPH differ from our modified SAPH in the same ways.…”
Section: Data Collectionmentioning
confidence: 98%
“…20 In a recent comparison between the elderly in the US and the UK, 39.4% and 32.1% of respondents respectively found screening to be unacceptable. 15 Refusal rates in high income countries vary from 19% 83 to 50% 84 , and among those agreeing to be screened, 47.7% of those screening positive refused further assessments, perceiving themselves to have no cognitive deficits; older blacks were more likely than whites to refuse screening. 84 Due to the low numbers of blacks in our sample, racial differences in acceptance of screening is yet to be determined locally.…”
Section: Challenges Of Screeningmentioning
confidence: 99%
“…15 Dementia screening enjoys a low priority in low and middle income country (LAMIC) healthcare systems that face considerable burdens relating to communicable diseases. 16,17 Fifty-eight percent of people with dementia currently live in LAMIC and this figure will increase to 70% in 2025 and to 71% by 2050.…”
Section: Introductionmentioning
confidence: 99%